Connectivity threshold of Bluetooth graphs. Issue 1 (4th September 2012) - Broutin, Nicolas; Devroye, Luc; Fraiman, Nicolas; Lugosi, Gábor
Abstract We study the connectivity properties of random Bluetooth graphs that model certain "ad hoc" wireless networks. The graphs are obtained as "irrigation subgraphs" of the well‐known random geometric graph model. There are two parameters that control the model: the radius r that determines the "visible neighbors" of each vertex and the number of edges c that each vertex is allowed to send to these. The randomness comes from the underlying distribution of vertices in space and from the choices of each vertex. We prove that no connectivity can take place with high probability for a range of parameters r, c and completely characterize the connectivity threshold (in c) for values of r close the critical value for connectivity in the underlying random geometric graph.Copyright © 2012 Wiley Periodicals, Inc. Random Struct. Alg., 44, 45–66, 2014